Peningkatan Keterampilan Proses Sains dan Hasil Belajar Siswa melalui Penerapan Model Problem-Based Learning pada Konsep Mutasi Kelas IPA 3 SMA Negeri 2 Sidrap - Akmal, Akmal (Universitas Negeri Makassar, 2019)
Abstract. The Aims of this research: 1) To find out the improvement of science process skills of students in exact sience 3 grade 12th through the application of a problem-based learning model in SMA Negeri 2 Sidenreng Rappang. 2) To find out the improvement of student learning outcomes on biology subjects through the application of the problem-based learning model in exact science 3 grade 12th at SMA Negeri 2 Sidnreng Rappang. The subjects in this study were students in exact science 3 grade 12th in SMA Negeri 2 Sidenreng Rappang in the academic year of 2017/2018 with 34 students consisting of 13 male students and 21 female students. Data collection on student process skills during the learning process takes place obtained from the results of subsequent observations of data on student learning outcomes obtained from the results of student evaluations conducted at the end of each cycle. To find out the results of student test evaluations conducted at the end of each cycle using quantitative analysis. Research results show that the application of the problem-based learning model can improve science process skills and learning outcomes of students in exact science 3 grade 12th in SMA Negeri 2 Sidenreng Rappang. Thus, it can be concluded that the application of the problem-based learning model in learning activities can improve science process skills and learning outcomes in Exact Science 3 grade12th in SMA Negeri 2 Sidrap.Keywords: problem-based learning model, the concept of mutations